Distribution of blue and sei whale vocalizations, and temperature - salinity characteristics from glider surveys in the Northern Chilean Patagonia mega-estuarine system - Buchan, Susannah J.; Gutiérrez, Laura; Baumgartner, Mark F.; Stafford, Kathleen M.; Ramirez, Nadin; Pizarro, Oscar; Cifuentes, Jose (Frontiers in Marine Science, 2022)
Northern Chilean Patagonia is a mega-estuarine system where oceanic waters mix with freshwater inputs in the coastal fjords, channels and gulfs. The aim of this study was to examine the distribution of blue and sei whales with respect to oceanographic conditions of the study area from the estuarine inner sea to the outer ocean. Ocean gliders were used, mounted with a hydrophone to determine acoustic presence of whales (Southeast Pacific and Antarctic blue whale song calls, and blue whales D-calls; sei whale downsweeps and upsweeps), and a temperature and salinity instrument. Four glider deployments were carried out in April 2018 and April-June 2019 navigating a total of 2817 kilometers during 2110 hours. To examine interannual variation, the average percentage of day with presence of calls was compared between years using the adjusted p-values for one-way ANOVA and descriptive statistics. To examine spatial variation between the hourly acoustic presence of blue whales and sei whales and temperature and salinity conditions, Generalized Linear Models (GLMs) were used. Salinities were higher in 2019 compared to 2018. Southeast Pacific blue whales produced song calls throughout the study area in both years, across estuarine and oceanic areas, but percentage of day with presence was higher in 2019 vs 2018. Percentage of day with presence of D-calls was similar between years, but higher in oceanic areas during both study periods. In contrast, the spatial pattern of sei whale acoustic presence was ambiguous and interannual variability was high, suggesting that sei whales preferred estuarine areas in 2018 and oceanic areas in 2019. We discuss possible explanations for observed acoustic presence in relation to foraging behavior and prey distribution.